PELATIHAN MEDIA PEMBELAJARAN BERBASIS AI UNTUK GURU PENDIDIKAN PANCASILA DI SMPN KABUPATEN MOJOKERTO: INISIATIF PENGABDIAN KEPADA MASYARAKAT - Listyaningsih; Nasution; Ita Mardiani Zain; Arief Sudrajat; Prasetya, Sukma; Dinar Rizky Listyaputri; Lidya Lestari Sitohang (Yayasan Penelitian dan Inovasi Sumatera (YPIS), 2025)
Rapid technological developments have had a significant impact on the learning process, particularly in integrating Artificial Intelligence (AI) into teaching practices. This study aimed to provide training to Pancasila Education teachers at Mojokerto State Junior High School on the creation of AI-based learning media. The goal was to empower teachers to effectively utilize AI tools to develop interactive and innovative learning content. The program, implemented by a team from Surabaya State University (UNESA), included theoretical and practical sessions focusing on AI platforms such as Canva AI, ChatGPT, and Bing Image Creator. The training aimed to improve teachers' competency in the digital transformation of Pancasila Education, while considering learner privacy and security. Feedback from participants indicated significant improvements in their skills and motivation to implement AI in the classroom, highlighting the importance of this type of training in fostering a more inclusive and innovative educational environment. The social impact of this training is seen in the increased ability of teachers to provide learning experiences that are more relevant to the needs of students in the 21st century, while supporting more inclusive learning, preparing students to face global challenges and future technologies.